Habermas’s Deliberative Structure of Discussion - الكفيري اعتدال; غسان علاء الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
Researching the deliberative structure of discussion according to Habermas must push us to trace the most important basic issues that Habermas addressed when he wanted to talk about the status of communicative actions that individuals establish among themselves in a deliberative framework in which they exchange viewpoints, opinions and ideas related to the issues they encounter in their daily lives that must be agreed upon and establish a rule of validity that shows to a large extent the importance of agreeing on those problems, which leads to solving them. However, this will not be possible unless there is a discussion at the public level that takes place among all segments of the people; a discussion whose steps are deeply and effectively established in a way that does not ignore people’s goals and interests, because when those interests are ignored, this means the absence of justifications for public discussion that is supposed to ultimately aim to achieve a shared human life among individuals that achieves their freedom of speech and action alike, not to mention that it gives them a sense of reassurance, security and human dignity.